Proyecto de factibilidad para la implementación de una estación de servicios gasolinera en la parroquia San Lucas del cantón Loja. - Suquilanda Saca, Enrique (2012)
The Service Station "GASDIMAX" CIA.LTDA. Fuel marketer, is structured by a field mapping consisting of Administrative and Service Area, Vending Area, Storage Area, Control Zone Download Zone thereof that are very important to fulfill the purpose of the Service Station, It also has technology that allows service quality and in large quantities, thus have a high bargaining power with suppliers of the product. In order to effect the smooth operation of the service station was financed with equity that is given in a 60.58% equivalent to $ 76.848,69 dollars and a loan equivalent to 39.42%, $ 50.000,00 Americans that was conducted in the Cooperative CoopMego a period of 5 years and an interest rate of 12%, payments are made every six months. In terms of sales revenue from the extra gas you get $ 383.727,51 U.S. dollars and the sale of diesel will have $ 269.620,97 dollars in revenue summary will have $ 653.348,48 dollars in the first year, according to measures for evaluating the project's NPV is greater than zero, with a discount factor of 12% is $ 10.200,38 U.S. dollars, the Internal Rate of Return is 14.92%, the sensitivity analysis allows us to increase 2.84% in 2.62% costs and declining revenue, the cost / benefit ratio interprets every dollar spent earns 0.06 cents and Capital Recovery Period will be in 4 years, 8 months and 12 days at therefore the project is feasible. In order to know the percentage of acceptance of the product / service in the parish of St. Luke's Loja, we conducted a market study by posing survey to determine the demand of fuel: Gasoline Extra and Diesel. For this reason the service station has decided to introduce this product / service in the parish, in order to be successful a service station and above all profitable. The fuel station services markets is differentiated by the quality, distribution efficiency and good service to users, which is why users acquire the product / service for your vehicle. The service station to publicize the product / service in the market based on one of the most used strategies such as advertising the same to be accomplished through radio commercials in Canton Saraguro SOUTHERN BORDER. All aspects taken into account previously have brought benefits that will result in the organization, be profitable and be a source of employment thus contributing to the socioeconomic development of the parish of San Lucas and the Country.